“Making treasure in heaven”: family chapels as a manifestation of the social power of urban elites (Portugal, 14th-17th centuries) - Ana Rita Rocha (Revista de História da Sociedade e da Cultura, 2025)
This article aims to analyse the family chapels founded by the urban elites of four Portuguese cities – Évora, Lisbon, Porto and Santarém – between the fourteenth and seventeenth centuries. Beginning by presenting a sociological characterisation of the founders and their families, according to their social and professional status, this will be followed by a definition of the profile of these individuals, based on the relationship they established with their ancestors and successors at the time of their souls’ suffrage. Lastly, the family chapels will come in to focus as a manifestation of the lineage’s memorialisation and an exhibition of the founders’ economic and social power, further to the investment they made in ornamentation and architecture. As such, an understanding of how the urban elites used these institutions in the context of the processes of social climbing they aimed for and how the chapels reflect the awareness of the power they achieved.